(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This research aims to numerous risks to the portfolio of the insurance company that arise from practicing the activity in general, and the risks arising from insurance contracts in particular, and what is the role of the company in the disclosure to help users (such as owners) to understand and concentration of risks in the financial reporting and identifying movable risks size to reinsurers that may affect the solvency of the portfolio and makes them at a given moment required to fulfill the obligations towards policyholders outweigh the financial capacity, which leads to stumble or bankruptcy. So I sought this research is to identify the extent of the obligation to disclose the accounting for this risk and the extent of their impact in reducing or reducing returns exposures in the portfolio of the insurance company, and in the light of this, the search to the basic premise reflect this relationship is based, and to achieve the aim of the research was conducted to measure the level of disclosure through the comparative analysis in accordance with the requirements of the standard international reporting number (4), accounting and al-Qaida Iraqi number (10) with what is available from the information in the financial reports national insurance Company, and the use of financial analysis index to measure the reinsurance portfolio company risks size, the study concluded that a number of conclusions concerning the practical side, the most important of a correlation and effect relationship between the level of accounting disclosure and the size of the risks of return for a portfolio of national insurance company,depending ontheconclusions of the research wasto provide a set of recommendations to the company in question, including the obligation to implement the standard international reporting number (4) in the financial reports of the national insurance company, in order to determine the yield and the risk posed to the company’s portfolio above, and give a clear picture of its clients about the nature of artistic activity.